Acute paraparesis syndrome after ruptured anterior communicating artery aneurysm. Issue 5 (4th February 2022) - Lee, Jong-Myong
Abstract : Abstract: Here, we describe a series of 7 patients who presented with acute paraparesis due to anterior communicating artery aneurysm rupture. This study aimed to assess the clinical and radiological factors associated with acute paraparesis syndrome caused by subarachnoid hemorrhage (SAH). Between June 2005 and December 2012, our institution consecutively treated 210 patients with anterior communicating aneurysm rupture within 24 hours after ictus. We divided the patients into 2 groups based on the presence (n = 7) and absence (n = 203) of acute paraparesis after anterior communicating aneurysm rupture. Diffusion-weighted magnetic resonance imaging revealed high intensity in the medial aspects of the bilateral frontal lobes in 3 patients. The mean third ventricular distance at the time of admission was 9.2 mm (range, 8–12.5 mm), and the mean bicaudate distance was 33.9 mm (range, 24–39 mm). There was a significant difference in the bicaudate distance ( P = .001) and third ventricle distance ( P = .001) between the 2 groups. Acute hydrocephalus and global cerebral edema (GCE) were confirmed radiologically in all patients in the acute paraparesis group. The presence of acute hydrocephalus ( P = .001) and GCE ( P = .003) were significantly different between the groups. Acute paraparesis syndrome after SAH is transient and gradually improves if the patient does not develop severe vasospasm. The present study demonstrates that acute paraparesis after SAH is associated with acute hydrocephalus and GCE.